Notch Signaling in Ischemic Damage and Fibrosis: Evidence and Clues from the Heart - Nistri, Silvia; Sassoli, Chiara; Bani, Daniele (Frontiers in Pharmacology, 2017)
Notch signaling is a major intercellular coordination mechanism highly conserved throughout evolution. In vertebrates, Notch signaling is physiologically involved in embryo development, including mesenchymal cell commitment, formation of heart tissues and angiogenesis. In post-natal life, Notch signaling is maintained as a key mechanism of cell-cell communication and its dysregulations have been found in pathological conditions such as ischemic and fibrotic diseases. In the heart, Notch takes part in the protective response to ischemia, being involved in pre- and postconditioning, reduction of reperfusion-induced oxidative stress and myocardial damage, and cardiomyogenesis. Conceivably, the cardioprotective effects of Notch may depend on neo-angiogenesis, thus blunting lethal myocardial ischemia, as well as on direct stimulation of cardiac cells to increase their resistance to injury. Another post-developmental adaptation of Notch signaling is fibrosis: being involved in the orientation of mesenchymal cell fate, Notch can modulate the differentiation of pro-fibrotic myofibroblasts, e.g. by reducing the effects of the profibrotic cytokine TGF-β. In conclusion, Notch can regulate the interactions between heart muscle and stromal cells and switch cardiac repair from a pro-fibrotic default pathway to a pro-cardiogenic one. These features make Notch signaling a suitable target for new cardiotropic therapies.